Korfball and gender issues: training strategies in coaches' perspective - Silva, Renata Laudares; Carmo, Elisangela Gisele do; Pacheco, José Pedro Scarpel; Fukushima, Rainara Lídice Mór; Rodrigues, Nara Heloisa; Schwartz, Gisele Maria (Revista Hipótese, 2019)
The present study investigated the coping strategies, adopted by korfball coaches from Brazil and Argentina, that minimize gender inequality. Coaches emphasized the importance of value education as well as the rules and goals of korfball as coping strategies to minimize gender inequality, favoring social equality. It demonstrated that in complex situations, coaches would adopt positions related to the dialogue, which would contribute to minimizing any occurrence of gender prejudice or discrimination that could compromise the team.
Keywords: Gender; Empowerment; Korfball; Coping; Sport